INFLUENCE OF LEADERSHIP, MOTIVATION, SALARY, AND INCENTIVE TOWARD EMPLOYEE PERFORMANCE PT. CEMENT PUGER JAYA RAYA SENTOSA - Fatim Matus Zahro; Agustin HP; Saiful Amin (MBA - Journal of Management and Business Aplication, 2020)
This study aims to determine the effect of leadership style, motivation, salary, and incentiveson the performance of employees of PT. Cement Puger Jaya Raya Sentosa. The population inthis study were 238 employees. The total sample of 110 respondents was selected based onproportional sampling. The data analysis method in this study uses multiple linear regressionanalysis. The results showed that the leadership style variable had a significant effect onemployee performance motivational variables have no significant effect on employeeperformance; Employee salary variable significantly influences employee performance;Motivational variables significantly influence employee performance at PT.Cement PugerJaya Raya Sentosa. While the incentive variable has a significant negative effect on employeeperformance at PT.Cement Puger Jaya Raya Sentosa.